2016
DOI: 10.1680/jadcr.16.00032
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and strength properties of lightweight concretes with the addition of aerogel particles

Abstract: The aim of this work was to examine the influence of the addition of aerogel particles on the properties of cement composites manufactured using fly ash aggregate. The composites were tested at three different concentrations of water saturation of the coarse aggregate. Moreover, two methods of aerogel particle application were usedplasticising the mix with superplasticiser and aerating with an air-entraining admixture. An assessment of the thermal properties was made during the first 28 d of curing of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 15 publications
0
15
0
6
Order By: Relevance
“…However, an exact opposite pore structure is required for high mechanical strength [1,4,5]. Similarly, when the effect of aerogel contribution on the concrete pore structure was investigated, it was found that the aerogel used at 20 % by volume can increase the total porosity value by 8.63 % through an additional pore volume created, especially at the porosity range of 10 -30 nm [12]. Studies that examine the change of pore structure in aerogelincorporated mortars under durability conditions are currently quite limited.…”
Section: Introductionmentioning
confidence: 97%
“…However, an exact opposite pore structure is required for high mechanical strength [1,4,5]. Similarly, when the effect of aerogel contribution on the concrete pore structure was investigated, it was found that the aerogel used at 20 % by volume can increase the total porosity value by 8.63 % through an additional pore volume created, especially at the porosity range of 10 -30 nm [12]. Studies that examine the change of pore structure in aerogelincorporated mortars under durability conditions are currently quite limited.…”
Section: Introductionmentioning
confidence: 97%
“…Noticeably, the values recorded for the concretes with aerogel are higher than those for the initial tests presented by Strzałkowski and Garbalińska, 2016. In the process of mixing, the aerogel particles were partially squeezed and fragmented, which is reflected in the results. In the initial tests, however, mixes of a maximum of 2 liters were prepared and the concrete was stirred manually, not mechanically.…”
Section: Fig 1 Apparent Total Porosity Of Fresh Mixesmentioning
confidence: 62%
“…It is common knowledge that the properties of given materials are determined by their internal structure and arrangement of pores, particularly those which can be filled with water in the liquid phase, cf. [7][8][9][10]. Table 2 lists the values of apparent density and moisture content by weight and volume specified for individual water-saturated blocks.…”
Section: Analysis Of the Results Of Strength Tests In Terms Of The Inmentioning
confidence: 99%